ANALISIS SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN (SIMPEG) SEBAGAI SISDM DI PEMERINTAH KOTA MAGELANG - Yulia, Elma; Ratnawati, Shinta (Politeknik Negeri Ambon, 2020)
Human Resources Information System (HRIS) provides information to all leadership in an organization. One of the efforts made by the Magelang City Government to create a good personnel administration system as well as in order responding to the rapid development of information and communication technology by developing the Management Information System Staffing (MISS). The purpose of this study is to find out what is meant by HRIS and describe it MISS Â at the Magelang City Government . In this study, the author uses design qualitative descriptive research. The results of this study indicate that the system can serving staffing administration becomes easier, such as employee transfers, promotions and retirement as well as ease in managing and completing various staffing documents and other requirements such as rank decree, position decree, STTPL and training needs.